2019
DOI: 10.1152/physiolgenomics.00037.2019
|View full text |Cite
|
Sign up to set email alerts
|

Acute suppression of insulin resistance-associated hepatic miR-29 in vivo improves glycemic control in adult mice

Abstract: MicroRNAs (miRNAs) are important posttranscriptional regulators of metabolism and energy homeostasis. Dysregulation of certain miRNAs in the liver has been shown to contribute to the pathogenesis of Type 2 diabetes (T2D), in part by impairing hepatic insulin sensitivity. By small RNA-sequencing analysis, we identified seven hepatic miRNAs (including miR-29b) that are consistently aberrantly expressed across five different rodent models of metabolic dysfunction that share the feature of insulin resistance (IR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
1
27
1
1
Order By: Relevance
“…We have demonstrated previously that one subcutaneous injection of LNA against miR-29 with this concentration effectively suppresses hepatic miR-29 expressions (Kurtz et al, 2015). We have also demonstrated in a previously published study that saline and LNA-scramble sequence (LNA-scr) exert similar effects on our physiological parameters of interest and therefore both can serve as control treatment for the LNA-29 in vivo study (Hung et al, 2019). We therefore used saline as control treatment in the present study.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…We have demonstrated previously that one subcutaneous injection of LNA against miR-29 with this concentration effectively suppresses hepatic miR-29 expressions (Kurtz et al, 2015). We have also demonstrated in a previously published study that saline and LNA-scramble sequence (LNA-scr) exert similar effects on our physiological parameters of interest and therefore both can serve as control treatment for the LNA-29 in vivo study (Hung et al, 2019). We therefore used saline as control treatment in the present study.…”
Section: Methodssupporting
confidence: 53%
“…For example, Enho , Igfbp2 , Lpl , and Sparc are upregulated by LNA29 irrespective of the presence of Sirt1 (Figure 3B) and are known to be involved in improving energy homeostasis and/or lipid metabolism (Bradshaw et al, 2003; Wheatcroft et al, 2007; Kumar et al, 2008; Nie et al, 2011; Ganesh Kumar et al, 2012; Chen et al, 2017). Indeed, Enho , Lpl , and Sparc have been shown to be directly targeted by miR-29 (Yang et al, 2016; Song et al, 2018; Hung et al, 2019) and therefore the suppression of miR-29 would be expected to increase the expression and activity of these genes. Igfbp2 , on the other hand, does not have predicted target sites for miR-29 and its upregulation by LNA29 is possibly through an indirect mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In myocytes, miR-29 reduces insulin sensitivity by repressing IRS-1 , a target which is also bound in adipose tissue 35 . HITS-CLIP also reveals miR-29 binding sites in Myo1c and Cav2 , two genes involved in downstream propagation of insulin signaling 36,37 , suggesting overlapping function with the insulin de-sensitizing effect of miR-29 in liver 38,39 . In heart, miR-29 suppresses fibrosis by targeting Col3a1, Fbn1 , and Eln 24 .…”
Section: Figmentioning
confidence: 96%
“…Most interestingly, the miR-29 family also likely plays a role in glycemic control. For example, Praveen Sethupathy and colleagues (16) recently reported that inhibition of miR-29b-3p in vivo resulted in improved glycemic control and reduced insulin resistance, thus supporting a critical role for miR-29 in both cholesterol and glucose metabolism in vivo. In addition, miR-29 has also been shown to play a critical role in glucose metabolism in pancreatic islets and b-cell functions.…”
Section: Recent Success Of Mirna Research In Cardiometabolic Diseasesmentioning
confidence: 99%